Stability Analysis of helicopter dynamics with incomplete information using MPC - Kudryavtseva Irina; Petrov Kirill (MATEC Web of Conferences, 2022)
The paper is devoted to the problem of seeking a helicopter motion control using MPC provided that the state vector is not fully observable. It is supposed that the helicopter motion is described by a dynamic system linearized near regimes with different fixed values of the forward speed. To solve the problem for an arbitrary value of the forward speed the interpolation strategy when the system matrices are decomposed in the basis of the finite functions is used. The proposed technique is applied to analyze dynamic behavior of three models of helicopters: ZD559-Lynx, SA330-Puma, S123-Bo105. The MPC approach permits to gain the stability of helicopters with complete and incomplete information in varying a time interval on which the system is under control and an interval over which a desired output is needed to achieve, initial conditions of a motion and values of the forward speed.